Impact of multiple insertions of two retroelements, ZAM and Idefix at an euchromatic locus. - Conte, C.; Calco, V.; Desset, S.; Leblanc, P.; Dastugue, B.; Vaury, C. (Genetica, 2000)
Transposable elements represent a large fraction of eukaryotic genomes and they are thought to play an important role in chromatin structure. ZAM and Idefix are two LTR-retrotransposons from Drosophila melanogaster very similar in structure to vertebrate retroviruses. In all the strains where their distribution has been studied, ZAM appears to be present exclusively in the intercalary heterochromatin while Idefix copies are mainly found in the centromeric heterochromatin with very few copies in euchromatin. Their distribution varies in a specific strain called RevI in which the mobilization of ZAM and Idefix is highly induced. In this strain, 15 copies of ZAM and 30 copies of Idefix are found on the chromosomal arms in addition to their usual distribution. Amongst the loci where new copies are detected, a hotspot for their insertion has been detected at the white locus where up to four elements occurred within a 3-kb fragment at the 5' end of this gene. This property of ZAM and Idefix to accumulate at a defined site provides an interesting paradigm to bring insight into the effect exerted by multiple insertions of transposable elements at an euchromatic locus.